Lattice-matched antiperovskite-perovskite system toward all-solid-state batteries - Daisuke Ito; Naoaki Kuwata; Seiji Takemoto; Kazuhiro Kamiguchi; Gen Hasegawa; Kazunori Takada (Nature Communications)
Abstract Inorganic solid electrolytes have emerged as promising candidates for realizing all-solid-state batteries because they eliminate flammable, low boiling-point liquids in lithium-ion battery cells, improving safety and cycle life. In this study, we present a highly lattice-matched composite solid electrolyte consisting of an antiperovskite-perovskite system, offering the benefits of both antiperovskites as melt-infiltratable solid electrolytes and perovskites as fast-ion conductors. Atomistic simulations predict significant lithium-ion diffusion at the interface between cubic Li2OHCl and Li0.31La0.56TiO3. The incorporation of fluorine enables room-temperature operation by stabilizing the high-temperature cubic phase of Li2OHCl1-xFx and reduces the lattice mismatch ratio to 0.8% at the interface through lattice contractions. The composite solid electrolyte was synthesized via pressure-assisted melt infiltration. The solid electrolyte effectively infiltrates conventional lithium-ion battery electrodes while maintaining a stable interface structure. Electrochemical testing demonstrates promising charge-discharge characteristics, including long cycle life and rate performance. Intricate infiltration of the solid electrolyte into an electrode structure composed of active materials with microcracks and high surface area enables stable operation by mitigating degradation phenomena typically observed in liquid electrolyte-based lithium-ion batteries.